Recycling processes and quality of secondary materials: Food for thought for waste-management-oriented life cycle assessment studies. (June 2018) - Rigamonti, Lucia; Niero, Monia; Haupt, Melanie; Grosso, Mario; Judl, Jáchym
Highlights: Modelling of avoided materials products is key in waste-management-oriented LCA study. Quality of recycled materials must be addressed. Down-cycling phenomena for typical waste materials are explained. Recommendations are given to enhance the modelling of the substitution of primary materials.